Evaluación inmunológica de un antígeno parasitario (Cooperia Curticei) en ovinos. - Ruiz Rodríguez, Samantha Isabella (2023)
The gastrointestinal parasitism in sheep represent productive and economic losses in sheep production in Ecuador, among the most important parasites is Cooperia curticei, that is a nematode that causes gastrointestinal disorders, anemia and even death. The objective of this research is evaluating the parasite load and the immune response of the inoculated sheep with the parasite antigen for Cooperia curticei by means of stool examination, serological tests (complete blood count and immunoglobulins A and E), and fleece quality. The research was carried out in the Cusualó neighborhood, Pujilí Canton, Cotopaxi Province, with 30 creole sheep between 8 months and 3 years of age, males and females. Based on the aforementioned, it was proceeded to perform coproparasitary, hematological and immunological analyzes pre and post inoculation of the animals. The pre-inoculation sheep presented Cooperia curticei eggs in their stool. After 48 days, stool tests were performed again, thus obtaining a significant difference <0.05, confirming the reduction of parasites in 22 sheep, while 8 were free of parasites. In IgA, was observed a decrease in 17 sheep post inoculation, however, there was no significant difference. The post-inoculation IgA results showed that 70% remained within normal parameters, with slight alterations within the ranges, however there was no significant difference. Regarding the hematological examination, a significant difference (p-value <0.05) was determined in all parameters except hematocrit and platelets; in the red line 6.67% of the sheep presented anemia prior to inoculation and after inoculation it was reduced to 50%, in the white line before inoculation 100% of the animals presented chronic inflammation and then after the inoculation 3.33% of the animals presented acute inflammation. The analysis of the fleece showed a significant difference (p-value<0.05) in fineness, undulations and inch average, parameters taken into account for fleece quality and industrialization, however, the other parameters did not show a significant difference.